Cutaneous silent periods in multiple system atrophy - Štětkářová, Ivana; Kofler, Markus; Majerová, Veronika (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2015)
AIM: The cutaneous silent period (CSP) is a spinal inhibitory reflex primarily mediated by A-delta fibers. Prolonged CSPs have been reported in patients with restless legs syndrome (RLS) and idiopathic Parkinson's disease (IPD). Dopaminergic medication normalizes the CSP, concurring with the effect of levodopa on CSPs. To date, CSPs have not been extensively studied in patients with multiple system atrophy (MSA). The purpose of this study was to confirm abnormal CSP findings in a group of MSA patients and to affirm the lack of influence of levodopa on CSPs during long-term treatment. METHODS: We investigated 15 patients (4 males, 11 females, age 58-71 years) who fulfilled the diagnostic criteria for possible MSA. Thirteen patients had predominant parkinsonian symptoms (MSA-P), 2 had predominant cerebellar signs (MSA-C). We recorded CSPs in thenar muscles following noxious digit II stimulation. Sixteen healthy volunteers (6 males, 10 females, range 24-56 years) served as control subjects for CSP recordings. RESULTS: Group average CSP onset was mildly delayed (P<0.01), whereas CSP end latency (P<0.001) were markedly delayed and CSP duration prolonged (P<0.001) in MSA patients compared to healthy controls. MSA patients on levodopa treatment did not differ in their CSPs from those without levodopa. The dose of levodopa did not correlate to any CSP parameter. CONCLUSION: The observed CSP prolongation corroborates previous findings in a limited number of MSA patients. The ineffectiveness of long-term levodopa on CSP abnormalities is consistent with its poor clinical effect in MSA.
Keywords: senioři; Spinal Cord Diseases; Multiple System Atrophy; abnormální reflex; Middle Aged; mužské pohlaví; studie případů a kontrol; Muscle, Skeletal; Reflex, Abnormal; nemoci míchy; ženské pohlaví; Reaction Time; Humans; reakční čas; kosterní svaly; Parkinsonian Disorders; parkinsonské poruchy; lidé středního věku; multisystémová atrofie; Case-Control Studies; Female; Aged; lidé; Male